2021
DOI: 10.3390/cells10113081
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hyaluronic Acid on Tendon Physiology and Its Clinical Application in Tendinopathies

Abstract: The physical–chemical, structural, hydrodynamic, and biological properties of hyaluronic acid within tendons are still poorly investigated. Medical history and clinical applications of hyaluronic acid for tendinopathies are still debated. In general, the properties of hyaluronic acid depend on several factors including molecular weight. Several preclinical and clinical experiences show a good efficacy and safety profile of hyaluronic acid, despite the absence of consensus in the literature regarding the classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 95 publications
(114 reference statements)
0
25
0
7
Order By: Relevance
“…Further policies are pharmacologically oriented [ 28 ], such as using biolubricants in order to enhance the gliding capacity [ 29 ]. Among natural lubricants, hyaluronic acid (HA) is highly promising [ 30 , 31 ] because it occurs as the main lubricating agent in the natural synovial fluid [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further policies are pharmacologically oriented [ 28 ], such as using biolubricants in order to enhance the gliding capacity [ 29 ]. Among natural lubricants, hyaluronic acid (HA) is highly promising [ 30 , 31 ] because it occurs as the main lubricating agent in the natural synovial fluid [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of ATRs is multifactorial, and several intrinsic and extrinsic risk factors can be identified. While age, sex, and systemic conditions are non-modifiable predictors of rupture, BMI, use of different types of drugs, and sport involvement represent modifiable risk factors [12][13][14]. Metabolic diseases, such as diabetes mellitus, hypercholesterolemia, thyroid disorders, and obesity, impair tendon health, leading to Achilles tendinopathy and predisposing one to ATR [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely demonstrated that the accumulation of reactive oxygen species (ROS) stimulates the intracellular antioxidant system, which is tightly regulated by Nrf2 (nuclear factor erythroid 2 (NF-E2)-related factor 2) [ 5 ], and that a functional tendon-repair failure might be strongly associated with the activation of the Nrf2 pathway [ 6 ]. Recently, hyaluronic acid (HA) has been suggested for the clinical management of tendinopathies [ 7 , 8 ]. Our previous studies demonstrated that different HA preparations, depending on their molecular weight, counteracted apoptosis under H 2 O 2 -induced OS [ 9 ], enhanced cell recovery from H 2 O 2 exposure in terms of decreased cytotoxicity and reduced Nrf2 expression, and increased the expression of the HA receptor CD44 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…HA, as one of the fundamental components of cartilage and tendons, contributes to their viscoelastic properties in vivo [ 8 , 11 , 12 ]. However, HA efficacy in the management of RCT is still debated and a comprehensive description of the underlying molecular mechanisms involved is still lacking [ 8 ].…”
Section: Introductionmentioning
confidence: 99%